Vieux-Conches (Eure), un site castral et son environnement (xie-xviiie siècle) - Tanguy Debaene (Archéologie Médiévale)
A topographical survey of the Vieux-Conches ditched site has revealed its vast potential. The data collected led us to extend the survey to the landscape, the village and to evidence of craft and farming activities conserved on the site. The survey shows spatial organization around three distinct poles: a castle, a parish enclosure and an area dedicated to crops / ploughing. This work was finalized by targeted surface cleaning which enabled us, amongst other things, to establish the plan of the Saint-Ouen church. The study of this site proves its long occupation (11th -18th centuries) and leads us to reconsider the written sources.